Khasinmännyn ei-parametrinen tuotosmalli - Maltamo, Matti; Eerikäinen, Kalle (Metsäntutkimuslaitos, 2001)
Seloste artikkelista: Maltamo, M. & Eerikäinen, K.2001. The Most Similar Neighbour reference in the yield prediction of Pinus kesiya stands in Zambia. Silva Fennica 35(4): 437–451.
Tutkimusseloste